FAKTOR –FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Christella Winata; Tony Sudirgo (Jurnal Paradigma Akuntansi, 2023)
This research purpose is to obtain empirical evidence the effect of liquidity, capital structure, dividend policy, profitability and firm size on firm value. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange in the period 2017-2019, using the purposive sampling method, the total sample obtained is 61 companies. Data processing techniques using Eviews 11.0 version software. The results of this research indicate that all independent variables simultaneously have a significant effect on firm value. The partialtest indicate that profitability has positive and significant effect on firm value while liquidity, capital structure, dividend policy and firm size have no significant effect on firm value.